Kepraktisan dan Efektivitas Media Flashcard Modifikasi pada Materi Interaksi antar Makhluk Hidup Bagi Siswa SMP/MTs - Qurrotul Uyuni; Noer Af'idah; Fajrul Falah (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2023)
Problems in education often occur due to a weak learning process, namely the lack of student interestduring the learning process. This is because most teachers direct students to understand theory only.One solution to this problem is the existence of learning media. This study aims to describe the resultsof the development of modified flashcard media based on its practicality and effectiveness. Thisresearch is a development research that uses the ADDIE model which stands for analysis, design,development, implementation, and evaluation. The subjects of this study were junior high schoolstudents in grade VII. Practical data was obtained from student observations when using the media andthe distribution of student response questionnaires after using the media. Then effectiveness data wasobtained from student postests after studying the interaction material among living things usingmodified flashcard media. From the results of this study, it was found that modified flashcard media isvery practical with an average score of 93.2% and very effective with an average score of 87.1%. Thusthis learning media is very well used in the material of interaction among living things.